Penerapan Perpajakan dalam Transaksi E-Commerce - Ismatul Khaliyah (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to analyze the implementation of taxation in e-commerce transactions in Indonesia using a literature review approach. The analysis is conducted by reviewing previous studies, academic literature, and relevant legal regulations. The main focus is to identify the level of tax compliance among e-commerce actors, the effectiveness of implemented fiscal policies, and the contribution of the e-commerce sector to state revenue. Additionally, the study examines the legal framework governing e-commerce taxation, including the General Tax Provisions Law (KUP), the Income Tax Law, and the Value Added Tax Law (PPN). This approach seeks to evaluate the alignment between taxation practices and existing legal provisions. The findings are expected to provide a comprehensive overview of tax implementation in the e-commerce sector and offer policy recommendations to support a more effective and equitable digital taxation system.